2023
DOI: 10.1186/s40359-023-01240-0
|View full text |Cite
|
Sign up to set email alerts
|

Media screen time use and mental health in school aged children during the pandemic

Abstract: Background Children’s screen time activity has increased significantly during the pandemic. Extended school closures and heightened parent stress are associated with children’s behavioural difficulties and time spent watching screens. The primary aim of this study was to determine which school and household factors were associated with challenging behaviours in Canadian schoolchildren during the COVID-19 pandemic. Methods This longitudinal survey s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Studies have indicated notable shifts in children's movement behaviour during pandemic-associated restrictions, including: reduced physical activity [3][4][5]; increased sedentary behaviour, particularly recreational screen time [3][4][5][6]; and heightened sleep duration [5][6][7]. Additionally, several international studies have suggested that changes in movement behaviours and pandemic-induced social distancing measures affect physical health and have implications for children's mental health, including depression [8][9][10], anxiety [8,9,11], well-being [12], and mood [13].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated notable shifts in children's movement behaviour during pandemic-associated restrictions, including: reduced physical activity [3][4][5]; increased sedentary behaviour, particularly recreational screen time [3][4][5][6]; and heightened sleep duration [5][6][7]. Additionally, several international studies have suggested that changes in movement behaviours and pandemic-induced social distancing measures affect physical health and have implications for children's mental health, including depression [8][9][10], anxiety [8,9,11], well-being [12], and mood [13].…”
Section: Introductionmentioning
confidence: 99%